Competence framework for the evaluation of professional teaching performance at the University of Costa Rica - Zamora Serrano, Evelyn (2024)
The consolidation of the culture of evaluation and quality at the University of Costa Rica (UCR) requires constant reflection on its evaluation strategies and mechanisms. The objective of this article is to present a proposal for the conceptualization of university teaching and professional teaching competence, as well as the dimensions that compose it, depending on the context and current needs, in order to establish recommendations regarding the updating of the professional profile and the process of evaluation of teaching performance at the UCR. The purpose is to strengthen this process, contribute to the improvement of the professional development of teachers and guide the processes of teacher training at the Institution. The research was conducted between 2021 and 2023, with the participation of 282 teachers from different areas of knowledge.. Regarding its approach, it was a qualitative and ideographic study, not generalizable or explanatory to other evaluative cases. It is a descriptive investigation with the use of bibliographic review techniques, group discussion and survey. The results reveal that the definition built for university teaching covers the aspects that are essential for good teaching and that all the characteristics that the literature addresses are contained in one of the dimensions suggested by the Center for Academic Assessment (CEA). It is concluded that it is advisable to use this definition as a theoretical foundation in new instruments for evaluating teacher performance and that the breadth of the competency dimensions makes its operationalization necessary.